Communication skills 2 : developing basic research and writing skills - Baraceros, Esther L. (Manila, Philippines : Rex Book Store, 2000)
You can therefore see in this book, Developing Basic Research and Writing Skills, review exercises on paragraph and composition writing, principles and practice exercises on interviewing, questionnaire survey, research paper, survey research, and business letter writing.
Paragraph and the Whole Composition (A Review) -- Writing a Research Paper -- The Interview as a Tool in Research -- Survery as Tool in Research -- The Business Letter -- Bibliography.
Includes bibliographical references.
Keywords: RESEARCH DEVELOPMENT -- WRITING SKILLS